Interpretasi Resiprokal dalam Pernikahan Adat Bajapuik Minangkabau Perspektif Qira’ah mubadalah - Nadhifah, Ainin; Yustafad, Yustafad; Muna, Nailal; Rafli, Mohammad (JOM, 2024)
Bajapuik is a unique marriage tradition of the Minangkabau people, in which the woman approaches the man to propose marriage. This tradition is rooted in the strong matrilineal system of Minangkabau culture. This study aims to examine the Bajapuik traditional marriage process and the reciprocal values within it from the perspective of qira'ah mubjadi, which emphasizes interconnectedness and partnership between men and women, parents and children, as well as inter-ethnic communities. This study employs a qualitative method with a phenomenological approach to understand the experiences and meanings behind this tradition. The findings indicate that the Bajapuik marriage procession consists of three stages: (1) the pre-wedding procession, (2) the wedding procession, and (3) the post-wedding procession. Additionally, there are three reciprocal values in Bajapuik traditional marriage: (1) the reciprocal relationship between children and parents, (2) the reciprocal relationship between the bride and groom, and (3) the reciprocal relationship between the two extended families. The theoretical implications of this study suggest that the qira'ah mubjadi perspective offers an alternative framework for understanding cultural practices that emphasize relational balance and social harmony in Minangkabau society.